Analisis Desentralisasi Fiskal Dalam Pandangan Ekonomi Islam - Yeyen Novita; Reni Indriani Agustine; Abdul Aziz Nugraha Pratama (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to analyze issues in fiscal decentralization and Islamic economic views on economic decentralization. This research is a literature study in which information is obtained from books, scientific papers, theses, dissertations, encyclopedias, the internet, and other sources. The results of this study indicate that the implementation of regional autonomy and fiscal decentralization are like two sides of a coin that cannot be separated. This is regulated in laws and regulations concerning regional government and concerning financial balances between the center and the regions. Many observers say that the system of decentralization and regional autonomy is much better than the system of centralized government. In the view of Islamic economics regarding economic decentralization which refers to fiscal decentralization, there are several elements of fiscal theory including: first, the Islamic economy consists of three economic sectors, namely, the private sector, the social/voluntary sector, and the public sector. Second, Zakat as the basis of the fiscal system. Third, the allocation, distribution and stabilization functions of the Islamic economy are processed and implemented through all these sectors together. Fourth, the role of the public sector compared to other sectors is minimal but important as long as it operates continuously to ensure optimal allocation of existing resources in society, distribution of income, and building stability.